2015
DOI: 10.1063/1.4936939
|View full text |Cite
|
Sign up to set email alerts
|

Wetting and dewetting of narrow hydrophobic channels by orthogonal electric fields: Structure, free energy, and dynamics for different water models

Abstract: Wetting and dewetting of a (6,6) carbon nanotube in presence of an orthogonal electric field of varying strengths are studied by means of molecular dynamics simulations using seven different models of water. We have looked at filling of the channel, occupancy and structure of water inside it, associated free energy profiles, and also dynamical properties like the time scales of collective dipole flipping and residence dynamics. For the current systems where the entire simulation box is under the electric field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 107 publications
3
23
0
Order By: Relevance
“…It is worthwhile to mention that different water models were considered in some of the earlier studies on passage of water through carbon nanotubes in presence of electric fields. [50,69] The SPC/E water model was found to give results which were qualitatively similar to those given by other water models. The permeation of ions and water molecules through nanopores on application of pressure has also been investigated in some recent studies.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…It is worthwhile to mention that different water models were considered in some of the earlier studies on passage of water through carbon nanotubes in presence of electric fields. [50,69] The SPC/E water model was found to give results which were qualitatively similar to those given by other water models. The permeation of ions and water molecules through nanopores on application of pressure has also been investigated in some recent studies.…”
Section: Discussionsupporting
confidence: 71%
“…We note that the applied electric field of the current study is similar or lower than the maximum field used in many earlier studies. [24,[44][45][46][47][48][49][50][51] The MD simulations were carried out for equilibration of 10 ns with no electric field and then for another 10 ns under an applied electric field using the GROMACS program. [52] F I G U R E 1 The simulations were carried out with a time step of 2 fs at a constant volume and temperature with Nosé-Hoover thermostat.…”
mentioning
confidence: 99%
“…Notwithstanding, we deliberately carried out these MD simulations in larger systems to avoid as much as possible finite-size effects (see Figure S2 in the Supporting Information); thus, our results should hold for bigger homogeneous systems, but care should be taken when extrapolating to transport phenomena in inhomogeneous systems. Further systematic studies assessing water models, box sizes, long-range electrostatic schemes, and inhomogeneous systems must be carried out to precisely define the threshold for relevant thermodynamics effects of external potentials on water, as done by others. , …”
Section: Resultsmentioning
confidence: 99%
“…It is also reported that the electric field can induce the evaporation of water confined in-between hydrophobic nanocavities immersed in aqueous solutions [37]. Furthermore, wetting and dewetting of narrow hydrophobic nanocavities induced by electric fields have been studied by Kayal and Chandra [39]. These studies have mainly focused on the system of either end of the nanopores in contact with a liquid water bath.…”
Section: Introductionmentioning
confidence: 99%